EMPOWERING EFL STUDENTS IN WRITING THROUGH PORTFOLIO-BASED INSTRUCTION - Permana, Sudarya (2013)
The present study is about empowering EFL students in writing through portfolios-based instruction. In this study, portfolios were conceptualized as an approach to teaching writing. They were defined as a selected collection of students' works that exhibited their efforts, progress, and achievements in an English writing class in one semester. Meanwhile, the term 'empowerment' was understood as the improvement in writing involving two aspects: lingual and personal empowerment. Lingual empowerment was the improvement of writing where students could produce an effective or proficient text, whereas personal empowerment was concerned with the improvement of writing in which students showed a positive attitude in developing the text and towards their writing performance. The present study was conducted in an English writing class at the tertiary level including fifteen student teachers as the participants. The study took place in one semester, and it employed an action research design. Data were gained from student text analyses, classroom observations, the use of questionnaire, and interview. Data were analyzed using a qualitative and quantitative strategy. The qualitative strategy was undertaken through text analyses and coding in data of student texts, classroom observations, and interview. On the other hand, the quantitative strategy was based on descriptive statistics with frequency counts to data of questionnaire. The findings revealed that, despite several limitations, portfolio-based instruction could empower EFL students in writing in both lingual and personal aspects. Regarding lingual aspect, students improved their writing in terms of idea development or organization, fluency or structure, word choice, and mechanics. Meanwhile, of personal aspect, students had a positive attitude in developing the text and towards their writing performance shown, among others, through confidence and motivation in completing the writing tasks.